Exploring the meaning of recovery‐oriented care: An action‐research study. (14th November 2014) - Kidd, Susan; Kenny, Amanda; McKinstry, Carol
Abstract The present study describes participants' perspectives of the meaning of recovery‐oriented care in developing services for people with psychosocial disability associated with mental illness. Participants were involved in a 12‐month cooperative inquiry action‐research group from August 2012 to July 2013, with six consumers, four clinicians, and a carer. A major finding was the importance of the facilitation of dialogue that acknowledged the asymmetrical power differences between participants. Thematically‐analysed data identified an overarching global theme: 'I want services to hear me'. The theme reflected a shared view that participation is important in service development. Actions included mapping the integration of consumer participation within a mental health service and developing workshops to support change. Addressing the asymmetrical power relationship inherent in traditional mental health design is important. Using participatory processes, structural discrimination is revealed, and tensions associated with clinical mental health services and psychiatric practice can be discussed. A partnership approach to service development enables the social determinants of health to be addressed more effectively, as well as supporting individual recovery. These approaches create the potential for genuine transformational change. Approaches that support coproduction and codesign have the potential to enable solutions.